Pembelajaran Dalam Jaringan (Daring) Terhadap Motivasi Belajar Siswa IPS SMA Negeri 6 Surakarta - Alma Ikara Praresti; Sudarno Sudarno; Harini Harini (Journal on Education, 2023)
This study aims to determina the effect of online learning on students learning motivation in class XI IPS and XII IPS SMA Negeri 6 Surakarta. This study uses a quantitative research method and uses questionnaire to collect the data. As for the sampling technique, this study uses proportionate random sampling. The population in this study are students in class XI IPS and XII IPS SMA Negeri 6 Surakarta for the academic year 2022/2023 as many ad 353 with a sample of 188 students. This research uses quantitative research methods. Data collection techniques use questionnaires were analyzed using simple linear regression analysis with a significance level of 5% which was processes with the SPSS 20.0 apllication for windows. The results of the study show that there is a positive and significant influence between online learning and learning motivation of students in class XI IPS and XII IPS SMA Negeri 6 Surakarta, which is shown from the t count > t table, namely 7,563 > 1.653.